Latin-american cities and present conflicts (2005)
This article proposes an inspection of the Latin-american cities at beginning of the XXI century from the conflict point of view. On one hand the cumulative conflicts that remain unsolved despite decades, which still require high-priority attention. Among others: the quality access to domiciliary public services, the opportune enjoyment of education and social programs and services, health, social welfare and housing, the exclusion, and social, economic, politic and physical-space segregation. Secondly the conflicts related to mobility forms, the political-administrative decentralization processes, hunger, misery and unemployment, new crimes style; the population’s size of cities with high concentration volumes and functions, and the urban violence. As well, it is present the dilemma about globalization and the local issue, the social agents influence, and the discussion on urban form and town planning. The article ends with several reflections on the approached aspects.